Assemblies of JAG1 and JAG2 determine tracheobronchial cell fate in mucosecretory lung disease - Susan D. Reynolds; Cynthia L. Hill; Alfahdah Alsudayri; Scott W. Lallier; Saranga Wijeratne; Zheng Hong Tan; Tendy Chiang; Estelle Cormet-Boyaka (JCI Insight, 2022)
Mucosecretory lung disease compromises airway epithelial function and is characterized by goblet cell hyperplasia and ciliated cell hypoplasia. Goblet and ciliated cell types are derived from tracheobronchial stem/progenitor cells via a Notch-dependent mechanism. Although specific arrays of Notch receptors regulate cell fate determination, the function of the ligands Jagged1 (JAG1) and JAG2 is unclear. This study examined JAG1 and JAG2 function using human air-liquid-interface cultures that were treated with γ-secretase complex (GSC) inhibitors, neutralizing peptides/antibodies, or WNT/β-catenin pathway antagonists/agonists. These experiments revealed that JAG1 and JAG2 regulated cell fate determination in the tracheobronchial epithelium; however, their roles did not adhere to simple necessity and sufficiency rules. Biochemical studies indicated that JAG1 and JAG2 underwent posttranslational modifications that resulted in generation of a JAG1 C-terminal peptide and regulated the abundance of full-length JAG2 on the cell surface. GSC and glycogen synthase kinase 3 were implicated in these posttranslational events, but WNT agonist/antagonist studies and RNA-Seq indicated a WNT-independent mechanism. Collectively, these data suggest that posttranslational modifications create distinct assemblies of JAG1 and JAG2, which regulate Notch signal strength and determine the fate of tracheobronchial stem/progenitor cells.